1266Novel formin homology 2 domain containing 3 (FHOD3) mutations associated with the pathogenesis of hypertrophic cardiomyopathy (HCM) in an Irish population. (18th June 2020) - Carron, J; O"brien, J; Gallagher, M; Mcgorrian, C; Galvin, J
Abstract: Background: The genetic cause of hypertrophic cardiomyopathy (HCM) remains unexplained in a substantial proportion of cases. Recent large sequencing studies suggest that, though not previously implicated, FHOD3 (a Formin protein responsible for sarcomere assembly) may have a role in the pathogenesis of HCM, particularly variants affecting a conserved small coil-coiled domain (amino acids 622 to 655). Aim: To investigate the relationship between novel FHOD3 mutations, previously classified as variants of uncertain significance (American College of Medical Genetics ACMG Class III), and the development of HCM.  Methods: A single center review of HCM probands carrying mutations in the FHOD3 gene was conducted. Existing HCM patients from the family heart screening clinic database were retrospectively reviewed. Frequency of FHOD3 mutations, segregation among family members and clinical characteristics of patients were reviewed. All genetic analysis was conducted via the same internationally validated next generation sequencing lab. Results: Of 367 HCM probands identified in our center, 9 (2.45%) were found to have ACMG Class III mutations affecting the FHOD3 gene. Five of these 9 probands (56%) displayed the same p.Arg637Gln mutation, while the remaining 4 (44%) carry the same p.Ile648Thr residue alteration. Both of these are rare mutations, found to be present in <1% of controls in previous large sequencing studies and not previously reported. Among probands with the p.Ile648Thr mutation, co-segregation was confirmed in one family, another first-degree relative in the same family having suffered a sudden cardiac death (HCM confirmed on autopsy). In those with the p.Arg367Gln mutation, a strong family history was observed in two separate families, 4 first-degree members having a confirmed HCM diagnosis. Carriers of both mutation types displayed varying degrees of disease severity with rates of non-sustained ventricular tachycardia and device implantation similar to other HCM cohorts (∼40%). Conclusions: FHOD3 is a novel gene, recently implicated in the pathogenesis of HCM, though not previously well described in the literature. Carrier frequency of FHOD3 mutations in the HCM population in our center is similar to that described in recent publication (1-2%), and all carry variants affecting the suspected small coil-coiled domain (amino-acids 622-625).